Sensitivity to Change and Patient‐Centricity of the Unified Multiple System Atrophy Rating Scale Items: A Data‐Driven Analysis. Issue 7 (25th March 2022) - Krismer, Florian; Seppi, Klaus; Jönsson, Linus; Åström, Daniel Oudin; Berger, Anna‐Karin; Simonsen, Jacob; Gordon, Mark Forrest; Wenning, Gregor K.; Poewe, Werner
Abstract: Background: The Unified Multiple System Atrophy Rating Scale (UMSARS) is a commonly used semiquantitative rating scale to assess symptoms and measure disease progression in multiple system atrophy (MSA). However, it is currently incompletely understood which UMSARS items are the most sensitive to change and most relevant to the patient. Objective: The objective of this study was to assess sensitivity to change and patient‐centricity of single UMSARS items. Methods: Data were taken from the European Multiple System Atrophy Study Group Natural History Study and the Rasagiline for Multiple System Atrophy trial. Sensitivity of change of an item of the UMSARS was assessed by calculation of a sensitivity‐to‐change ratio using its mean slope of progression divided by the standard deviation of the slope when modeling its progression over time. Patient‐centricity was assessed through correlation of UMSARS items with quality‐of‐life measures. Results: Progression rates above the mean in at least one of the two studies examined here were seen for seven items of UMSARS I and 11 items of UMSARS II. These items related to key motor functions such as swallowing, speech, handwriting, cutting food, hygiene, and dressing or walking, whereas items related to autonomic dysfunction were generally less sensitive to change in either data set. More UMSARS I items were identified as patient‐centric compared with UMSARS II items, and items most strongly impacting patients' quality of life were those affecting verbal communication skills, personal hygiene, and walking. Conclusion: The present results illustrate the potential to optimize the UMSARS to enhance sensitivity to change and patient centricity. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society